Collective works, Festschrifts, series, symposia, etc. - The Editors, - (Nordic Archaeological Abstracts - NAA, 2002)
The list contains collective works, etc., the titles of which are followed by an asterix in the abstract heading. Proceedings of major Nordic symposia and series of Nordic material publications abstracted in this volume are also listed.